EDUKASI PEMBUATAN LAPORAN KEUANGAN SEDERHANA PADA KELOMPOK IBU PKK DESA PANDEYAN KECAMATAN TASIKMADU - Prastiwi, Iin Emy; Enggar Priska Pratiwi; Farit Naditya Listyawan; Diffa Aryatna Ulim Pradana; Dilla Andreani Kusuma Dewi; Fany Nur Zabrina; Merliana Dewi Hastuti (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
Abstract: Community service is an effort to make a positivecontribution to society through the application of knowledge and skills. One of the community service activities carried out is preparing simple financial reports for PKK mothers. This financial report helps PKK mothers in managing household finances and increases their understanding of the importance of financial recording. This article will explain the method for making simple financial reports, the results, as well as a discussion regarding the benefits and challenges faced. Conclusions and recommendations will also be presented as an effort to increase the effectiveness of this community service programme